An effective protocol to isolate and mechanically test silk fibers spun by Osmia lignaria Say (Hymenoptera: Megachilidae) fifth instar larvae - Oran Wasserman; Jackson J. Morley; Mary-Kate F. Williams; Brianne E. Bell; Diana L. Cox-Foster; Justin A. Jones (PLoS ONE, 2025)
Silk, a remarkable protein-based fiber spun by various arthropod lineages, has been prized for millennia, with the cocoon silk of domesticated silkworms and spiders being the most utilized and extensively studied. There is limited information on how silk can be used to investigate biology, development, and health in other silk-producing species, particularly for solitary bees such as Osmia lignaria Say (Hymenoptera: Megachilidae). Osmia lignaria, an increasingly managed solitary pollinator, produces silk cocoons during the fifth instar larval stage. We have developed a minimally invasive protocol to isolate and mechanically test O. lignaria silk fibers using a 3-D printed well plate system for rearing and two specific isolation techniques. Our protocol allows for collecting individual fibers directly from silk-spinning larvae between silk initiation and cocoon formation without preventing subsequent cocoon development, enabling silk characterization as part of larger rearing and developmental studies. For this study, isolated fibers were mounted on C-cards, facilitating diameter measurement using a microscope and mechanical testing with an MTS Synergie 100 tensile testing instrument. We successfully isolated and tested the mechanical properties of naturally spun silk from O. lignaria, with 20 fibers isolated and mechanically tested from seven larvae. Further examination of isolated silk can reveal physical, molecular, chemical, and morphological characteristics, advancing our understanding of bee silk properties and their role in bee biology, evolution, and nutritional status. This protocol provides a practical tool for researchers to isolate and study silk from silk-producing bee species.